Factors associated with mechanical restraint in the hospital environment: a cross-sectional study - Souza,Lívia Maria da Silva (2019)
ABSTRACT Objective: To estimate the prevalence of mechanical restraint in the hospital environment and the factors associated with its performance. Method: A cross-sectional, observational study with patients from a public hospital from the medical clinic, surgical clinic and intensive care unit evaluated by descriptive, univariate and multivariate analyses. Results: One hundred eleven (111) patients participated in the study. The prevalence of mechanical restraint was 51.4%; bilateral rails on the bed were used in 100% of the restraints, and bilateral wrist restraints were also observed in 29.8%. The most common justifications were the risk of falls (100.0%) and the risk of non-scheduled removal of invasive devices (57.9%). The restrained patients differ significantly from those not restrained by the following associated factors: male gender; age; stroke diagnosis; the hospitalization unit; ambulation capacity; the use of sedative medication; and the use of invasive devices. Conclusion: This study estimated a high mechanical restraint prevalence in the hospital environment and determined factors associated with the risk of a patient being restrained. A medical restraint evaluation team is recommended for an in-depth analysis of indication and therapy.